Exploring the Resilience of Vocational Training Instructors: Validating Resilience Measurement for Effective Coping in Education and Career Development Challenges - I Wayan Eka Sudarmawan; I Made Hadi Purnantara; Miko Andi Wardana (SAFE-Network, 2023)
This research presents a comprehensive exploration of vocational training instructors at Training Centers (LPK) in Denpasar, focusing on the validation of the 10-item CD-RISC scale as a measure of resilience. Utilizing SPSS software for discriminant item analysis, the study confirmed the suitability of all scale items, establishing their reliability in assessing resilience within the unique context of vocational training. The calculated corrected item-total correlations indicated a robust relationship between individual items and the overall scale. Cronbach's Alpha coefficients, consistently high at 0.963 both overall and based on standardized items, underscored the internal consistency of the 10-item CD-RISC scale. This research contributes to the understanding of resilience among vocational training instructors, emphasizing the importance of tailored measurement tools for specific contexts. The affirmed reliability of the scale suggests its utility for future research endeavors aimed at enhancing the resilience of vocational training instructors in Denpasar. Beyond academic implications, this study holds practical value for improving training programs and supporting instructors in navigating the challenges inherent in their profession.